Semisynthesis of esters and oxime esters/sulfonates from furyl-ring-based acetylation derivatives of fraxinellone as insecticidal agents. Issue 45 (26th May 2017) - Guo, Yong; Yang, Ruige; Xu, Hui
Abstract : Two compounds9a and10i exhibited the most promising pesticidal activity against early 3rd-instar larvae of Mythimna separata . Their structure–activity relationships were also observed. Abstract : In continuation of our program to discover new natural-product-based crop protection agents, we prepared a series of esters and oxime esters/sulfonates from furyl-ring-based acetylation derivatives as pesticidal agents by structural modification of fraxinellone, a biorenewable degraded limonoid isolated from Meliaceae and Rutaceae plants. The structural assignment was based on the spectroscopic and X-ray analysis data. Their insecticidal activity was evaluated against a crop-threatening agricultural insect pest, Mythimna separata Walker. Among all derivatives, compounds9a and10i exhibited the most promising pesticidal activity. Their structure–activity relationships were also discussed.